Does Preoperative Anal Physiology Testing or Ultrasonography Predict Clinical Outcome With Sacral Neuromodulation for Fecal Incontinence?. Issue 2 (February 2016) - Quezada, Yarini; Whiteside, James L.; Rice, Tracy; Karram, Mickey; Rafferty, Janice F.; Paquette, Ian M.
Abstract : Obstet Gynecol Surv 2016;71(2):74–76 Symptoms of fecal incontinence (FI) are common in women and have a profound effect on self-esteem and overall quality of life. A number of new treatments for FI have been investigated over the past several years.